The use of artificial intelligence in interactive virtual reality adaptive environments with real-time biofeedback applied to phobias psychotherapy - Gomes, Paulo Veloso (2023)
Exposure therapy is a type of psychotherapy where the patient is gradually exposed to a fear situation. Patients may present different degrees of phobia, and the degree of phobia of each patient changes throughout the treatment. The use of Interactive Virtual Reality Adaptive Environments, where the interaction is personalized through real-time biofeedback mechanisms, allows the environment to adapt to the patients and their evolution throughout the treatment. The Artificial Intelligence affective algorithms continuously monitor the patient’s behavioral data and physiological responses to adjust the intensity and number of the stimuli. This real-time adaptation aims to personalize and optimize the exposure process, gradually desensitizing patients to their fears